The Musician As Entrepreneur, 1700-1914 : Managers, Charlatans, and Idealists. - Weber, William E (Indiana University Press, 2004)
By uncovering the ways in which musicians such as Telemann, Beethoven, Paganini, and Liszt conducted their daily business, the authors reveal how musicians reshaped the frameworks of musical culture and, in the process, the nature of the music itself.